2011
DOI: 10.2486/indhealth.ms1236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Conditions on Manual Performance while Wearing Petroleum Industry Protective Clothing

Abstract: The purpose of this study was to investigate manual performance and thermal responses during low work intensity in persons wearing standard protective clothing in the petroleum industry when they were exposed to a range of temperatures (5, -5, -15 and -25°C) that are relevant to environmental conditions for petroleum industry personnel in northern regions. Twelve men participated in the study. Protective clothing was adjusted for the given cold exposure according to current practices. The subjects performed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Skilled dexterity performance is required in the meatpacking (Oksa et al 2006, Sormunen et al 2009), fishing (Lundqvist et al 1990) and petroleum (Wiggen et al 2011) industries, and is vital to the completion of military missions. Randomised and/or counterbalanced trials occurring over several laboratory visits seek to minimise learning effects and participant anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Skilled dexterity performance is required in the meatpacking (Oksa et al 2006, Sormunen et al 2009), fishing (Lundqvist et al 1990) and petroleum (Wiggen et al 2011) industries, and is vital to the completion of military missions. Randomised and/or counterbalanced trials occurring over several laboratory visits seek to minimise learning effects and participant anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Local cooling of the extremities has a detrimental effect on manual performance [5], but minimizes the total heat loss and maintains temperature in core areas. A study performed on petroleum workers in cold conditions showed that finger temperature was an important indicator of hand and finger dexterity and that finger skin temperatures below 15°C resulted in impaired manual performance [7]. Real-time information about skin temperatures on hands and fingers could function as an early warning to prevent the risk of reduced manual performance and hence ensure safe and proper accomplishment of tasks.…”
Section: A Electronic Sensor System and Integration In Jacketmentioning
confidence: 99%
“…The most obvious effects of work in the cold are distraction and reduced manual dexterity associated with local cooling of finger and hands [5]. Finger and hand temperatures of 15°C and below are closely related to reduced manual performance [6] [7]. There are several methods for assessment of cold stress.…”
Section: Introductionmentioning
confidence: 99%
“…Hand finger temperature is considered to be a significant indicator of hand and finger dexterity. In this regard, previous studies propose that a finger skin temperature below 20°C can lead to manual performance loss (Wiggen, Heen, Faerevik, & Reinertsen, ).…”
Section: Introductionmentioning
confidence: 96%